The effect of using of a school participatory learning management model to promote online learning management competency of Pre-teachers of Faculty of Education Silpakorn University - Sithsungnoen, Chanasith (Journal of Humanities and Social Sciences Review, 2025)
This research aimed to examine the effectiveness of a participatory learning management model implemented in schools to enhance the online learning management competencies of student teachers. The specific objectives were: (1) to study the knowledge of student teachers in organizing online learning activities, (2) to examine their ability to design online learning activities, (3) to investigate their ability to conduct online learning activities, and (4) to assess their satisfaction with the participatory learning management model. The model was implemented through four stages of participatory activity: co-thinking, co-implementation, co-evaluation, and co-benefiting. The sample consisted of 40 second-year undergraduate student teachers majoring in Early Childhood Education at the Faculty of Education, Silpakorn University. Participants were selected using purposive sampling. The research instruments included a knowledge and understanding test, an evaluation form for learning design ability, an evaluation form for learning management ability, and a questionnaire to assess student teachers’ opinions toward the participatory learning management model. Data were analyzed using mean and standard deviation. The research findings revealed that (1) the student teachers' knowledge regarding learning management techniques, media production and innovation development, assessment and evaluation, learning activity design, and classroom management was at a good level; (2) their ability to design learning activities (experience arrangement) was at a very good level; (3) their ability to manage learning activities (experience arrangement) was at a good level; and (4) their satisfaction with the participatory learning management model was at a high level.